2008
DOI: 10.4269/ajtmh.2008.78.40
|View full text |Cite
|
Sign up to set email alerts
|

A Major Trichinellosis Outbreak Suggesting a High Endemicity of Trichinella Infection in Northern Laos

Abstract: Trichinellosis is an important and under-recognized food-borne zoonosis in Southeast Asia. After 30 years of no reports, a small outbreak was described in Central Lao PDR (Laos) in 2003. Here we report a large outbreak of at least 650 estimated patients in Udomxay (northern Laos) in June 2005. Trichinella ELISA assays on serum from 133 patients and Western blot assays on 16 patients were positive in 67.6% and 81.2%, respectively. No deaths were recorded. Consumption of uncooked or fermented pork at funeral and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 16 publications
4
47
1
Order By: Relevance
“…3 The identification of Trichinella larvae isolated from human biopsies and pigs from the 2012 outbreak as T. spiralis is in agreement with literature data that show that this species is the most widespread species infecting domestic pigs in southeast Asia, China, and most of the other world regions. 4,8,24,[33][34][35] The identification of the etiological agent as T. spiralis is also in agreement with the severity of the clinical picture, which resulted in the death of eight patients in the course of three of five outbreaks.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…3 The identification of Trichinella larvae isolated from human biopsies and pigs from the 2012 outbreak as T. spiralis is in agreement with literature data that show that this species is the most widespread species infecting domestic pigs in southeast Asia, China, and most of the other world regions. 4,8,24,[33][34][35] The identification of the etiological agent as T. spiralis is also in agreement with the severity of the clinical picture, which resulted in the death of eight patients in the course of three of five outbreaks.…”
Section: Discussionsupporting
confidence: 52%
“…4,23,24 In the course of the last 50 years, there was an active animal black market between the borders of these countries, which favored the spread of Trichinella-infected pigs in the area. In Vietnam, excluding the outbreak of trichinellosis in the Saigon area caused by the consumption of pork from a wild boar, 11,12 Trichinella infections were documented only in domestic pigs and humans of the north Vietnamese provinces.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the database PubMed, there are two official reports on big outbreaks of trichinellosis in Laos and all has just been reported within this decade [9 -10]. Barennes et al concluded that "trichinellosis may be an under-recognized but important endemic disease in Laos and reinforces the need to urgently implement veterinary and educational programs [10]." Nevertheless, it is believed that the problem is still required management in this country.…”
Section: The Situation In Laosmentioning
confidence: 99%